(untitled) (Journal of Governance and Development (JGD), 2014)
This article reviews the South Korean Democratic Labour Party’s (DLP) anti-neoliberal campaigns of the 2000s. While the centrist government implemented abortive economic reform and pro-capitalist labour policies, the DLP had a great window of opportunity to replace the centrist tendency with a moderate socialist program. Contrary to expectations, the DLP’s counter neoliberalism campaigns were unsuccessful as the party’s campaigns went through within an anti-capitalist, anti-imperialist struggle which resembled the radical Latin American leftist parties in the 1970s. Due mainly to this radical strategy, the DLP was unable to create a broad coalition with civil movements and the centre-left tendency. The DLP’s radical anti-neoliberalism campaign was unsuited to the Korean constituency and the party was defeated in a series of presidential elections.